An evaluation of moral education’s capabilities in enriching student’s moral behaviour - Tham, Jia Hao; Mustakim, Siti Salina; Krishnasamy, Thilagavathy; Minghat, Asnul Dahar; Suhid, Asmawati; Abd. Manaf, Umi Kalthom; Tam, Suet Yet (Science and Engineering Research Support Society, 2020)
This research aims to explore the capability of Moral Education in enriching student’s moral behaviour in Melaka secondary school through four research questions, 1) What are the policy, aims and objectives of Moral Education developed by the Ministry of Education in secondary schools?, 2) What are the scope and quality of support, resources, and training in the implementation of Moral Education?, 3) To what extent have the curriculum performance and monitoring, and instructional practices been employed in the implementation of Moral Education?, and 4) To what extent have the actual outcomes of Moral Education been achieved in secondary schools? Qualitative research design is applied in this research with the participation of two moral teachers and five upper secondary students. The data collection techniques apply in this research included document analysis and semi-structured interviews. The data collected are analyzed manually. This research discovered that the Moral Education is effective in enhancing students’ moral behavior. The syllabus of Moral Education is suitable for secondary school students. The curriculum should be continued with some improvement.